Code Switching and Code Mixing by The Government of Bali - Ni Putu Ayu Yuni Sugiantari (RETORIKA: Jurnal Ilmu Bahasa, 2018)
Abstract—This study examines code-switching and code mixing realized in the interactional activities undertaken by govermental leaders in the Denpasar City of Bali Province, Indonesia. Typically I reveal the language types used by bilingual and multingual governments during code swithing and code mixing events as well as investigating their leading factors. The study was designed using qualitative research method. The results of this study indicate that code mixing dan code-switching undertaken by the leaders in the governmental area of Denpasar city involves 3 types of language, namely Balinese, Indonesian, and English. An element of code mixing filler occurring during interactional process of the leaders is tangible words and phrases. Leading factors to such phenomena of code mixing and code-switching are: language ability, speech topics, speech participants, speech situations, prestige; and creating regional or religious nuances. Keywords: Code mixing; code switching; governmental leader